2020
DOI: 10.1002/app.49675
|View full text |Cite
|
Sign up to set email alerts
|

Compatibility improvement of poly(lactic acid)/thermoplastic starch blown films using acetylated starch

Abstract: The present research aims to improve the compatibility between relatively hydrophobic poly(lactic acid) (PLA) and hydrophilic thermoplastic starch (TPS) and the properties of the PLA/TPS blends by replacing TPS from native cassava starch (TPSN) with TPS from acetylated starch (TPSA). The effects of the degree of acetylation (DA) of acetylated starch, that is, 0.021, 0.031, and 0.074, on the morphological characteristics and properties of PLA/TPS blend are investigated. The melt blends of PLA and TPS with a wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 63 publications
5
17
0
Order By: Relevance
“…These interactions are generated between the starch and the PLA chains that cause a nucleation effect. The interactions allow the structure greater freedom of movement [ 37 ]. Additionally, other authors have observed that the T g is reduced in PLA/TPS blends with respect to PLA, due to a plasticizing effect exerted by TPS on the PLA matrix [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These interactions are generated between the starch and the PLA chains that cause a nucleation effect. The interactions allow the structure greater freedom of movement [ 37 ]. Additionally, other authors have observed that the T g is reduced in PLA/TPS blends with respect to PLA, due to a plasticizing effect exerted by TPS on the PLA matrix [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, certain degrees of acetylation in starch restrict intermolecular interactions (formation of hydrogen bonds), and as a consequence increase hydrophobicity and chain mobility. This causes fluidity in the material, optimal for potential use as flexible packaging [ 35 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, pure thermoplastic starch has high hydrophilicity and poor mechanical property compared with other thermoplastic polymers, which hindered its application. To overcome these shortcomings, blending other biopolymers with TPS represent an alternative method to prepare biodegradable bioplastics [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…The polymer blended with starch act as a plasticizer, reducing the interaction between adjacent starch chains. Poly(lactic acid), 13 poly(vinyl alcohol), 14 and poly(caprolactone) 15 are examples of polymers blended with starch. Although this method usually succeeds in improving the properties of starch-based materials, chemical modification reactions are still the simplest and preferred alternative for minimizing the drawbacks of starch.…”
Section: Introductionmentioning
confidence: 99%